2018
DOI: 10.1088/1367-2630/aad70f
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations disclose early stages of the photo-activation of cryptochrome 4

Abstract: Birds appear to be equipped with a light-dependent, radical-pair-based magnetic compass that relies on truly quantum processes. While the identity of the sensory protein has remained speculative, cryptochrome 4 has recently been identified as the most auspicious candidate. Here, we report on allatom molecular dynamics (MD) simulations addressing the structural reorganisations that accompany the photoreduction of the flavin cofactor in the European robin cryptochrome 4 (ErCry4). Extensive MD simulations reveal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 86 publications
(181 reference statements)
4
40
0
Order By: Relevance
“…MD simulations have also suggested for the FAD cofactor roles other than photoreduction and CRY activation: the FAD presence would confer to the receptor a more fluctuation-prone behavior, thus decreasing the amount of necessary light input energy for CRY activation (Masiero et al, 2014). Recent studies performed on a longer timescale have revealed that following photoactivation, FAD is released from the FAD-binding pocket, providing evidence that CRY undergoes an inactivation reaction rather than a photocycle (Kutta et al, 2018), in agreement with the reported irreversible nature of the light-induced conformational changes (Ozturk et al, 2009;Kattnig et al, 2018;Lin et al, 2018). The active form of CRY is then able to bind the circadian components TIMELESS (Ceriani et al, 1999) and PERIOD (Rosato et al, 2001).…”
Section: Structure and Photoactivationsupporting
confidence: 67%
“…MD simulations have also suggested for the FAD cofactor roles other than photoreduction and CRY activation: the FAD presence would confer to the receptor a more fluctuation-prone behavior, thus decreasing the amount of necessary light input energy for CRY activation (Masiero et al, 2014). Recent studies performed on a longer timescale have revealed that following photoactivation, FAD is released from the FAD-binding pocket, providing evidence that CRY undergoes an inactivation reaction rather than a photocycle (Kutta et al, 2018), in agreement with the reported irreversible nature of the light-induced conformational changes (Ozturk et al, 2009;Kattnig et al, 2018;Lin et al, 2018). The active form of CRY is then able to bind the circadian components TIMELESS (Ceriani et al, 1999) and PERIOD (Rosato et al, 2001).…”
Section: Structure and Photoactivationsupporting
confidence: 67%
“…As a directional response to magnetic fields does not fulfil a known function in plants, this could be interpreted as an outcome of the lack of a corresponding evolutionary incentive. Note, however, that while WC is strong in cryptochromes with a tetrad, the orientation of WC in the homology model for the avian cryptochrome 4 [75,76] is less optimal than that extracted from the crystal structure of the Drosophila cryptochrome. This observation could inspire a variety of interpretations: the homology model or the current approach may have limited predictive power, another driver must be considered, anisotropy is an inappropriate measure of sensitivity or that a different radical pair is at play, to name but a few.…”
Section: Orientational Magnetosensitivity In [F •− W •+ ]mentioning
confidence: 95%
“…We have also compared the tryptophans of the triad/tetrad for the established crystal structures of cryptochromes with bound flavin and a homology model of cryptochrome 4 from the European Robin [75,76]. The magnetic field effect anisotropies have been summarized in Table 1.…”
Section: Flavin-tryptophan Radical Pairs With Variable Relative Orienmentioning
confidence: 99%
See 1 more Smart Citation
“…The graphene layers with deposited amino acids were neutralized in water using NaCl by assuming the height of the simulation box equal to 45Å. The protocol was largely adopted from earlier MD simulation on similar systems [17][18][19]. Particle mesh Ewald method was used to treat the long-range electrostatics [20,21] with a cutoff distance of 12Å.…”
Section: Classical Molecular Dynamics Simulationsmentioning
confidence: 99%